« Qu’avez-vous fait de vos vingt ans ? » Militantismes marocains du 23-mars (1965) au 20 février (2011) - Frédéric Vairel (L’Année du Maghreb)
The purpose of this article is to examine the tight political sequence that began with the first demonstrations of February 20 and ended with the November 2011 early legislative elections. The sequence reflects the renewed integration of the Moroccan regime and its protesters into the dynamics of international protest. The institutionalization of the Moroccan protest space from which the February 20 movement emerged, and the effects of learning for protesters and security forces alike were the reason for extremely cautions behaviors in an effort to avoid escalation. In other words, regardless of the radical posture claimed by members of the movement - or coined by their critics in an attempt to delegitimize them - the issue of mobilization and public controversy was nothing more than the reform of the monarchy. Political parties and unions offered only limited support to mobilization, when they did not oppose it : the 2011 demonstrations were an accurate indicator of the straitjacket process in the field of established politics.